A sex-specific association between incident radiographic osteoarthritis of hip or knee and incident peripheral arterial calcifications: 8-year prospective data from Cohort Hip and Cohort Knee (CHECK). Issue 11 (November 2017) - Gielis, W.P.; Welsing, P.M.J.; van Spil, W.E.; Runhaar, J.; Weinans, H.; de Jong, P.A.
Summary: Objectives: There is sparse evidence for a relationship between cardiovascular disease (CVD) and osteoarthritis (OA). We investigated the association between incidence of arterial calcifications and incidence of radiographic knee and/or hip OA. Design: We used baseline and 8-year follow-up data of Cohort Hip and Cohort Knee (CHECK). Knees and hips were either Kellgren–Lawrence (KL) grade 0 or 1 at baseline. Arterial calcifications were scored on hip and knee radiographs using a four-grade scale. Scores were summed for patient-level analyses. To investigate incidence, participants with arterial calcifications at baseline or missing follow-up were excluded. Incident OA was defined per joint as KL ≥ 2 or prosthesis at year eight. The association between incidenct of arterial calcifications and incident OA was studied using mixed-effects logistic regression. Results: Of 763 participants included, 623 (82%) were women. Mean (sd) age was 56 (5.1) years, mean (sd) body mass index (BMI) 26.2 (4.1) kg/m 2 . Arterial calcifications developed in 174 participants (283 joints). OA developed in 456 participants (778 joints). Sex modified the association between arterial calcification and OA. In women, incident arterial calcification around a joint was positively associated with incident OA in that joint (adjusted OR 2.51 (95% CI 1.57–4.03)). In men, no association was observed on joint-level, but at patient-level the arterial calcification sum score was negatively associated with incident OA (adjusted OR per point increase 0.70 (95% CI 0.54–0.90)) indicating a systemic effect. Conclusions: We observed sex-dependent associations between incident arterial calcification and incident radiographic knee and/or hip OA, which differs between joint- and patient-level.